Bahasa Indonesia Bahasa Indonesia: Bahasa Indonesia - Halasanni Agustina Pardede; Dea Annisa (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to examine whether independent commissioners, audit committees, and corporate governance affect the integrity of financial reports in various industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 to 2020. The type of research conducted was quantitative research using the quantitative method. associative. The research sample was determined using a purposive sampling technique, so as to produce a sample of 41 companies with a total of 123 observational data. The analytical test used is descriptive statistical analysis test, panel data regression model selection, panel data regression model selection test, classical assumption test, panel data regression analysis and hypothesis testing. The results in this study were tested using the panel data regression model which aims to obtain an overall picture of the influence of independent commissioners, audit committees, and corporate governance on the integrity of financial statements. Overall the research results are presented in tabular form to make it easier to read and understand. The results of the study prove that independent commissioners, audit committees and corporate governance have proven to have a significant effect on the integrity of financial statements.